Norbert Cyffer, Erwin Ebermann and Georg Ziegelmeyer (eds.) 2009. Negation Patterns in West African languages - Pasch, Helma (Afrikanistik online, 2010)
The present volume is a most welcome contribution to the investigation of negation in African languages of non-Bantu language groups. It aims at filling a gap in the study of African languages, since – as several of the authors state - negation has so far only been given little attention: "the structural and conceptual function of negation was often given little consideration in the grammatical description of African languages, though in many African languages we are confronted with a remarkable complexity of negation patterns" (Cyffer, p.72). Negation is a highly complex matter and interacts with other grammatical categories.
Keywords: Gur; Hausa; Jukun; Kanuri; Negation; focus